The Pure Element of Time - Beʼer, Haim (Book collections on Project MUSE., 2003)
A rich and evocative autobiographical novel about a writer's development. With his keen eye and opulent writing style, Haim Be'er turns the story of his childhood and maturity into a complex and gripping work of art.